2006
DOI: 10.1111/j.0902-4441.2006.t01-1-ejh2888.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet autoantibodies are common in hepatitis C infection, irrespective of the presence of thrombocytopenia

Abstract: While platelet autoantibodies are common in individuals with HCV infection, their detection does not assist in the diagnosis of immune thrombocytopenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…41,42 There have been conflicting data reported with respect to the presence of specific antibodies in platelet eluates from patients with HCVrelated ITP. 41,42,47,48 In the latter report, 66% of patients infected with HCV had detectable anti-platelet glycoprotein antibodies. However, their presence did not correlate with the patients' platelet counts.…”
Section: Hcv Infectionmentioning
confidence: 89%
See 1 more Smart Citation
“…41,42 There have been conflicting data reported with respect to the presence of specific antibodies in platelet eluates from patients with HCVrelated ITP. 41,42,47,48 In the latter report, 66% of patients infected with HCV had detectable anti-platelet glycoprotein antibodies. However, their presence did not correlate with the patients' platelet counts.…”
Section: Hcv Infectionmentioning
confidence: 89%
“…However, their presence did not correlate with the patients' platelet counts. 48 A similar frequency of antiplatelet glycoprotein antibodies was found in patients with alcoholic cirrhosis, indicating these antibodies were not specific for HCV infection. 48 …”
Section: Hcv Infectionmentioning
confidence: 90%
“…We did not include antiplatelet antibodies in our study because of prior evidence that they are not responsible for thrombocytopenia in CHC, but there is conflicting evidence on this point. 11, 18 One possible mechanism affecting the platelet count in CHC is that HCV infects the bone marrow. Another potential mechanism is that platelets are increasingly sequestered in a fibrotic liver, though this was not apparent in our examination of liver biopsies stained for platelets.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous reports of CHC patients have found that the presence of antiplatelet antibodies did not affect the platelet count. 18 Vascular endothelial dysfunction has also been found to play a role in thrombocytopenia in patients with CHC. Namely, von Willebrand Factor (vWF) and thrombomodulin have been found to be significantly correlated with the platelet count in patients with CHC.…”
Section: Introductionmentioning
confidence: 99%
“…increase gradually as the severity of liver disease increases, suggesting that prolonged HCV infection causes marked immune system abnormalities. 8,13 Antiplatelet-antibody titers were found to be high in most of the patients with chronic HCV infection.…”
Section: Conflicts Of Interestmentioning
confidence: 99%